Malay ethics in Nasib Melayu’s poem in the view of Raja Ali Haji Paul Ricoeur’s hermeneutic study - Nurhidayah, Frida; Wulandari, Yosi (Universitas Ahmad Dahlan, 2024)
Malay ethics is closely related to human behavior and actions in the social environment. Behavior related to ethics reflects the knowledge possessed by a person in determining good and bad things. The development of society, especially Malay is very important to be able to understand the ethical mindset. The Malay community views ethics as a very important thing to consider in showing the identity of customs against the rules of tradition and the surrounding environment. Malay ethics can be found in some of the Malay poems that generally develop in the region of the Sumatera community such as the Nasib Melayu’s poem. A poem is defined as a literary work that has meaning and is poetic in nature. Poem is an old form of literary work that has existed since the emergence of Islamic civilization in Indonesia. The purpose of this study is to describe the Malay ethics in Nasib Melayu’s poem contained in the book entitled Kitab Syair, Sejarah, Konsep, dan Contohnya according to Raja Ali Haji's view. This research uses a type of qualitative research that focuses on descriptive. The data collection method uses observation methods with reading and recording techniques. Data analysis in this research uses Paul Ricoeur's Hermeneutics study. The results showed that Malay ethics in Nasib Melayu’s poem contained four ethical elements, namely the morality of the ruler, obedience to sharia, language, and moral environment. Thus, it can be concluded that Nasib Melayu’s poem contains Malay ethics based on Raja Ali Haji's view.